Children’s Safety Olympics – A Preventive Project of the Police Directorate Maribor with Partners - Viltužnik, Rafael (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
In the paper, we present the preventive project of the Police Directorate Maribor, the Children's Safety Olympics (CSO). CSO is a competition for elementary school students in the knowledge of rules for preventing negative safety phenomena, and eliminating their causes and consequences. In addition to testing knowledge and skills, CSO intends to present all public authorities and services operating in the field of safety and security. At each preliminary competition and final event, children can get familiar with the attractions and equipment of the Police, Slovenian Armed Forces, healthcare, fire departments and other units in the field of protection and rescue, etc. Within the framework of CSO, the sports competition “Štengijada” is also organised every year. The paper presents a brief historical outline, the course of the competition, the method of connecting safety stakeholders and other interested individuals and companies, and the purpose and effects of implementing this preventive project.